Fluid Distribution Analysis of Kite Sail for Application on Ship - Amiadji; Arief, Irfan Syarif; Fadhlurrahman, Zaki Rizqi (International Journal of Marine Engineering Innovation and Research, 2025)
The increasing number of operating ships resulted in high air pollution from the combustion of the ship's engine. Efforts to utilize alternative energy to reduce ship engine work have been done, one of them is using unlimited alternative energy that is wind where one of its application of is the application of new ships sail, kite sail as auxiliary system of ship propulsion . In this final project purposed to find out the value of aerodynamic force of kite sail and power it can generated , with a CFD method that uses 3 kite sail design forms, rectangular, triangular, and elliptical, with an area of 160 m2 this models are simulated at wind speed variations from 13.4 m / s up 15.82 m / s and angel of attack variation of 15.20, and 25. From the variation obtained the total aerodynamic force generated can reach 28.73 kN in rectangular shape, 30.79 kN of Elipsical shape, and 27.55 kN of triangular shape, on variant Angel Of attack 25. From the value of the aerodynamic force, each kite sail capable of generating power, on a rectangular kite sail of up to 263.02 kW, an elipsical 276.75 kW, and a triangular 252.63 kW.